Cerek Elektrik Berbasis Flash Heat Treatment: Penerapan Teknologi Praktis Dalam Mencegah Transmisi HIV Dari Ibu Ke Bayi Di Masa Menyusui - Zulfikar, Eddy (Essential: Essence of Scientific Medical Journal; Vol 17 No 1 (2019): Volume 17 No. 1 (Januari-Juni 2019) ESSENTIAL: Essence Of Scientific Medical Journal, 2019)
Introduction: HIV/AIDS is still become a major problem in global health, especially for the women population. HIV-infected women have a greater risk of transmitting HIV to their babies through the Mother to Child Transmission (MTCT) which mostly occurs during breastfeeding. Prevention of MTCT of HIV by replacing exclusive breastfeeding with formula milk is still controversial, considering that breast milk contains antibodies and other protective nutrients that can protect the babies from various infectious diseases. Therefore, the latest effective method is needed to prevent transmission of HIV from mother to child during breastfeeding, namely Flash Heat Treatment (FHT). Discussion : See above the total 30 breast milk samples tested, it was found that the average HIV concentration in breast milk without heating was 8,266 copies/ml with a mean log of 3.45 copies/ml, compared to flash heated milk which shows an almost undetectable level of HIV, which is under 400 copies/ml. This proves that breast milk with a flash heated method can inactivate HIV in breast milk and prevent the transmission of HIV from mother to child during breastfeeding. In addition, the application of FHT in the form of electric kettles can be promising to achieve stabilization and standardization of the use of FHT that is appropriate at the level of housewives. Conclusion: The use of FHT-based electric kettles in breast milk could become an effective and affordable method in preventing HIV transmission from mother to child during breastfeeding, especially in low to middle income countries.   Keywords: electric kettles, FHT, HIV, MTCT